The cascade of hypertension care in Cambodia: evidence from a cross-sectional population-based survey - Savina Chham; Veerle Buffel; Josefien Van Olmen; Srean Chhim; Por Ir; Edwin Wouters (BMC, 2022)
Abstract Background Hypertension (HTN) is a leading cause of cardiovascular diseases and deaths globally. To respond to the high HTN prevalence (23.5% among adults aged 40-69 years in 2016) in Cambodia, the government (and donors) established innovative interventions to improve access to screening, care, and treatment at different public health system and community levels. We assessed the effectiveness of these interventions and resulting health outcomes through a cascade of HTN care and explored key determinants. Methods We performed a population-based survey among 5070 individuals aged ≥ 40 years to generate a cascade of HTN care in Cambodia. The cascade, built with conditional approach, shows the patients' flow in the health system and where they are lost (dropped out) along the steps: (i) prevalence, (ii) screening, (iii) diagnosis, (iv) treatment in the last twelve months, (v) treatment in the last three months, and (vi) HTN being under control. The profile of people dropping out from each bar of the cascade was determined by multivariate logistic regression. Results The prevalence of HTN (i) among study participants was 35.2%, of which 81.91% had their blood pressure (BP) measured in the last three years (ii). Over 63.72% of those screened were diagnosed by healthcare professionals as hypertensive patients (iii). Among these, 56.19% received treatment in the last twelve months (iv) and 54.26% received follow-up treatment in the last three months (v). Only 35.8% of treated people had their BP under control (vi). Males, those aged ≥ 40 years, and from poorer households had lower odds to receive screening, diagnosis, and treatment. Lower odds to have their BP under-control were found in males, those from poor and rich quintiles, having HTN < five years, and receiving treatment at a private facility. Conclusions Overall, people with HTN are lost along the cascade, suggesting limited access to appropriate screening, diagnosis, and treatment and resulting poor health outcomes, especially among those who are male, aged 40-49 years, from poorer households, and visiting a private facility. Efforts to improve the quality of facility-based and community-based interventions are needed to prevent inequitable drops along the cascade of care.